Advanced services architectures for Internet telephony a critical overview. - Glitho, R.H (IEEE Network : the magazine of global information exchange)
Advanced services are differentiating factors and crucial to service providers' survival and success. Examples are credit card calling, call forwarding, and toll-free calling. In classical telephony's early days their implementation was embedded in switching software, and this hindered fast deployment. A more modern architecture known as the intelligent network (IN) was born in the 1980s, allowing implementation in separate nodes, resulting in faster deployment of new services. Two tracks are emerging for Internet telephony: one from the ITU-T and the other from the IETF. As far as advanced services are concerned, the ITU-T track offers a rather archaic architecture, reminiscent of the early days of classical telephony. On the other hand, the IETF architecture, although more modern, does have a few pitfalls. There is plenty of room for improvement to both. This article scrutinizes the ITU-T and IETF advanced services architectures for Internet telephony. Salient features are reviewed and weaknesses pinpointed. Although these architectures are constantly evolving, alternatives may emerge. We provide a discussion of two potential alternatives: IN-based architectures and mobile-agent-based architectures